THE EUROPEAN UNION DEFORESTATION-FREE REGULATION (EUDR) POLICY: RESISTANCE, IMPACT, AND CHALLENGES FOR PALM OIL PRODUCING COUNTRIES - Muhammad Solihin; Fitriana, Kurnia Nur; Paulus Adrianus K.L Ratumakin; Safrida (Natapraja, 2024)
This study examines the implications of the European Union's Deforestation-Free Regulation (EUDR) 2025 policy on Indonesia and Malaysia as major producers of land-based commodities. This study analyzes three critical aspects: the impact of implementation, forms of resistance, and challenges in its implementation. This study employs secondary data (2020-2024) sourced from Google Scholar, Scopus, government publications, and news portals. Thematic coding was applied for data analysis, with triangulation across academic journals, media reports, and policy documents ensuring validity. The EUDR has triggered systematic resistance through diplomatic alliances, WTO lawsuits, national policy adjustments, and farmer protests. Its impacts span multiple dimensions: regulatory, economic, social, and environmental. This study developed an institutional theory framework to understand the impact of global environmental policies, empirically by mapping the strategic responses of developing countries, and practically through concrete policy recommendations in the form of harmonization of certification standards, development of inclusive funding systems, and evidence-based diplomacy strategies. The main findings of the study emphasize the importance of a just transition approach that considers the specific capacities and needs of producer countries in the Global South in implementing global environmental policies.